Development of a Microneedle Swab for Acquisition of Genomic DNA From Buccal Cells - Kim, Yun-Seo; Kim, JeongHyeon; Na, Woonsung; Sung, Gil-Hwan; Baek, Seung-Ki; Kim, Yun Kyoung; Kim, Gyeong Ryeong; Hu, Hae-Jin; Park, Jung-Hwan (Frontiers in Bioengineering and Biotechnology, 2022)
A swab is a tool for obtaining buccal DNA from buccal mucus for biological analysis. The acquisition of a sufficient amount and high quality of DNA is an important factor in determining the accuracy of a diagnosis. A microneedle swab (MN swab) was developed to obtain more oral mucosal tissues non-invasively. Eight types of MN swabs were prepared with varying combinations of patterns (zigzag or straight), number of MNs, intervals of MNs, and sharpness of tips. When MN swab was applied up to 10 times, the tissue amount and DNA yield increased compared to commercial swabs. A zigzag pattern of microneedles was found to be more efficient than a straight pattern, and increasing the number of microneedles in an array increased the DNA yield. The MN swab collected about twice the DNA compared to the commercial swab. In an in vivo test using mini-pigs, the lower cycle threshold values of mucosal samples collected with MN swabs compared to samples collected with commercial swabs indicated that a greater amount of DNA was collected for SNP genotyping. A polymer MN swab is easy to manufacture by a single molding process, and it has a greater sampling capacity than existing commercial swabs.